A Spanish Calvinist Church in Elizabethan London, 1559–65 - Hauben, Paul J. (Church history, 1965)
As a result of Father Albert J. Loomie's recent volume, The Spanish Elizabethans, this descriptive phrase would appear to be a dramatic designation for English Catholic exiles in Philip II's dominions. However, it seems equally appropriate to use the appelation with reference to a much less known and smaller group, the Spanish Calvinist refugees of Elizabethan London. The latter were organized into a congregation in the early 1560's by Cassiodoro de Reina; to a very considerable extent the success and collapse of this church parallels its pastor's career, as we shall see.